Bimbingan Membaca Al-Qur’an untuk Anak dan Remaja sebagai Upaya Peningkatan Kualitas Spiritual Masyarakat - Risni, Titin Widya; Hendy, Hendy; Vitasmoro, Pamadya; Nuzul, Hayatun (Jurnal Ragam Pengabdian, 2026)
The dynamics of the modern era bring significant value shifts in the behavior of children and adolescents, often having an impact on the decline of the spiritual quality of society. This study aims to analyze the effectiveness of the Qur'an reading guidance program as a strategic instrument in improving the spiritual quality of the younger generation and its implications for the socio-religious order. Using a descriptive qualitative method with a field study approach, data was collected through observation, in-depth interviews, and documentation of religious guidance programs. The results of the study show that guidance in reading the Qur'an carried out in a structured manner not only improves Arabic and tajweed literacy, but also stimulates spiritual intelligence (SQ), controlling emotions, and forming moral character. The implications of this micro-level spiritual strengthening (children and adolescents) contribute directly to the increase in social and religious awareness of the community on a macro level. The synergy between interactive learning methods, the active role of parents, and the support of surrounding institutions is the key to the success of this program.